Salvage of a TRAM breast reconstruction flap using the retrograde internal mammary artery system - Sameena Hassan; Tuabin Rasheed; Anna Raurell (Indian Journal of Plastic Surgery)
Background: Free tissue transfer provides an optimal means for breast reconstruction in creating an aesthetically natural appearance that is durable over time. The choice of donor vessels vary from surgeon to surgeon, but the internal mammary axis is one of the most popular choices together with the thoracodorsal vessels. Aims and Results: We present the case of a salvaged free transverse rectus abdominis myocutaneous breast reconstruction in which end-to-end antegrade anastomosis to the internal mammary artery (IMA) was not possible due to frail vessel walls, but retrograde anastomosis to the IMA and antegrade anastomosis of internal mammary vessel resulted in a perfused and viable flap. Conclusion: We suggest the use of the retrograde internal mammary arterial system for microsurgical anastomosis when the anterograde flow is not adequate, the vessel wall is friable, and when other more common options are not available.